UT PICTURA POESIS: ENTRE PALAVRA E IMAGEM (Revista Apotheke, 2017)
This paper aims to discuss the relations between words and images, offering a revision of an antique polemic called ut pictura poesis (painting is like poetry), derived from an Horace`s statement which was cited in different art`s history periods. The reflexion tries do understand the relations between words and images in the contemporary art`s approach, beginning in its more remote roots. The text starts with a This paper aims to discuss the relations between words and images, offering a revision of an antique polemic called ut pictura poesis (painting is like poetry), derived from an Horace`s statement which was cited in different art`s history periods. The reflexion tries do understand the relations between words and images in the contemporary art`s approach, beginning in its more remote roots. The text starts with a reading from an oeuvre by Marila Dardot, a Brazilian artist, which is called Demão. In this work, text and image co-exist, both collaborating in the same way to the final result. Putting these questions, the paper tries to discuss the relations between poetry and painting, bringing the historical aspects from the matter in different periods, including some antique manifestations, as well as renaissance`s, eighteen century`s and from the avant- garde`s period.
Keywords: visual art; painting; poetry; UT PICTURA POESIS